224 Outcomes of stage IV melanoma in the era of immunotherapy: a national cancer database (NCDB) analysis. (9th November 2020) - Sussman, Tamara; Wei, Wei; Funchain, Pauline; Gastman, Brian
Abstract : Background: Immunotherapy (IO) has revolutionized the treatment landscape for metastatic melanoma and is now the mainstay of treatment since the approval of ipilimumab in 2011 and anti-PD-1 therapies (nivolumab and pembrolizumab) in 2015. The majority of data stems from trials that have specific inclusion criteria, and often exclude important populations. In this analysis, we present the first real-world evidence of outcomes for stage IV patients with cutaneous melanoma receiving IO from 2015–2016 and factors associated with receipt of IO, and compare these outcomes with patients receiving IO (likely interferon and interleukin-2) from 2004–2010, and IO (addition of ipilimumab) from 2011–2014. Methods: NCDB was analyzed to identify stage IV patients with melanoma from 2004–2016. Patients were categorized into receipt of IO or not during time periods from 2004–2010, 2011–2014, and 2015–2016. Patients treated with and without IO were propensity matched on age, gender, and stage. Overall survival (OS) analysis was done by Kaplan-Meier and Cox proportional hazard models; log-rank test was used for between-group OS comparisons. Results: A total of 21, 696 patients with stage IV melanoma were analyzed from 2004–2016. Overall, patients (n = 3, 852) who received IO had improved median survival (mOS 17.2 vs. 7.3 mos; p<0.0001). All patients had improved median survival as time progressed (mOS 7.9 mos in 2004–2010 vs. 9.1 mos 2011–2014 vs. 11.9 mos 2015–2016; p<0.0001). Among patients who received IO, 2-year OS significantly improved by 2015 (40% [95%CI, 37–42%] for both 2004–2010 and 2011–2014 vs. 48% [95%CI, 44–51%] in 2015; p=0.01) (figure 1). In the overall cohort, younger patients (<60 years), female gender, private insurance, no comorbidities, and treatment at academic/research centers were associated with better OS (p<0.0001 for all). Receipt of radiation therapy and lack of surgery were both associated with worse OS (p<0.0001 for both). Race and area of residence (metro/rural/urban) were not associated with differences in OS (p=0.09 and p=0.07, respectively). In 2015–2016, receipt of IO was associated with younger age (<60 years), lack of comorbidities, private insurance, higher median income (=38, 000), residence in metro area, and treatment at academic/research centers (p<0.0001 for all) (table 1). Conclusions: Survival was improved in stage IV patients with melanoma receiving IO, especially in 2015, with the approvals of pembrolizumab and nivolumab. Our findings are consistent with recent trials, like KEYNOTE 006 and CheckMate 067 where 2-year OS for anti-PD-1 therapy was 55% and 60%, respectively. 1, 2 Significant socioeconomic factors may impact receipt of IO and survival. References: Robert C, Ribas A, Schachter J, et al. Pembrolizumab versus ipilimumab in advanced melanoma (KEYNOTE-006): post-hoc 5-year results from an open-label, multicentre, randomised, controlled, phase 3 study. Lancet Oncol 2019; 20: 1239–1251. Wolchok JD, Chiarion-Sileni V, Gonzalez R, et al . Overall Survival with Combined Nivolumab and Ipilimumab in Advanced Melanoma. N Engl J Med 2017; 377: 1345–1356.